Contraception and PrEP knowledge, attitudes, and practices among adolescent girls and young women in Nampula, Mozambique. - Allison Hsu; Joana Falcao; Ricardino Zandamela; Allison Zerbe; Jennifer M Zech; Eduarda Pimentel de Gusmao; Elizabeth Stephanz; Mirriah Vitale; Elaine J Abrams (PLOS Global Public Health)
Despite widespread availability of ART and PrEP, HIV incidence among adolescent girls and young women (AGYW) in Mozambique remains amongst the highest in Africa. Similarly, modern contraception methods are broadly available in the public sector, but high rates of unplanned pregnancies persist. We explored AGYW's sexual behavior and knowledge of sexual and reproductive health, and HIV prevention practices in Nampula, Mozambique. Between May-June 2022, we conducted a cross-sectional survey among a convenience sample of AGYW 15-25 years whose self-reported HIV status was negative or unknown receiving care at three adolescent health clinics in Nampula province. Information on demographics, sexual behavior, HIV, and contraception and PrEP knowledge and attitudes was collected. Responses were analyzed using descriptive statistics. Of 200 AGYW (median age: 19 years, interquartile range: 17-21.3 years), 55% were in school, 32% completed secondary school and 81% had never been employed. Overall, 77% reported ever having had sex and 26% reported being <16 years at first sex. Nearly all respondents knew about condoms; only half had used a condom at last sex. Male condoms (62%), withdrawal (35%), and implants (25%) were the most commonly previously used contraceptive methods. AGYW were most interested in trying implants (18%), injectables (12%), and the pill (11%), though 31% reported not being interested in trying any new contraceptive method. Respondents had accurate general HIV knowledge; only 26% reported had ever heard of PrEP and 2% reported previous use. However, 64% expressed interest in using PrEP daily pills and 76% in long-acting injectables. AGYW in Nampula reported low usage of modern contraceptive methods and poor knowledge of PrEP. AGYW expressed interest in trying contraception and PrEP and showed positive attitudes toward PrEP usage. More widespread education around family planning and HIV prevention is needed to reduce barriers around improving sexual health among AGYW in Mozambique.